Child Prostitution In The Media Vortex - Rr. Pramesthi Ratnaningtyas (ULTIMA Comm, 2023)
Child prostitution is still exciting news for the media because it is a commodity that will be ready for consumption by the readers. Prostitution as a form of exploitation of children is carried out sexually and economically. This condition cannot be separated from the position of children who are seen as weak. They are also considered far from mature, so they are easily trapped in the lure that puts them in an unfavorable situation. Okezone.com captures these events and phenomena to be used as news ready for consumption. The events experienced by children have become a commodity to be commodified so that they can benefit the media. In particular, if the news related to child prostitution can make the media visited by many people. This study seeks to see how Okezone.com describes the position of children in the practice of prostitution in its reporting. Using the discourse analysis method developed by Sara Mills as an analytical knife and agenda setting, this study finds that the selected sources cannot be separated from the media agenda when carrying out their journalistic work. Children are still placed as objects to be told and trapped in body manipulation for prostitution.